Increasing Student Capacity Through Online ‘Education And Training’ Of Collaboration Of Thematic In Disaster Risk Reduction - Maghfirah, Nuril; Rahmawaty, Arie Asih; Indrapertiwi, Centauri (Community Development: Jurnal Pengembangan Masyarakat Islam, 2024)
The COVID-19 pandemic has changed our activities in all sectors, especially education. The policy of physical distancing forced the Government to implement an online learning system from home (daring), one of the learning methods that utilizes technology. There was a slight increase in student capacity after participating in a collaborative online guest lecture on disaster management, a subject of the Study Program of Islamic Community Development, IAIN Kudus, by inviting practitioners from the Regional Disaster Management Agency (BPBD) to one meeting. In line with the curriculum of independent study on an independent campus, Guest lectures can realize the optimum result in increasing student capacity in disaster risk reduction through technology, which “Education and Training” can learn through online thematic collaboration. This research aims to determine students' increasing capacity in disaster risk reduction through it. It targeted 30 students of the study program of Islamic community development, IAIN Kudus, who have or are studying disaster management subject. For three days (6JPL), the lecture used application technology like Zoom and Quizizz application. This research used a quantitative approach with a T-test (comparing pretest and posttest scores on knowledge) using SPSS v26. The study results have a higher mean value for the posttest (73.20) than the pretest (34.06). The mean paired samples test result was -39.14, with a significant value of p <0.01. It shows an essential difference before and after online education and training in collaboration. On the other hand, it means to increase students' capacity for disaster risk reduction.